Outlaw. Issue 2 (20th November 2019) - Polson, Michael
Abstract: Framed around the case of cannabis cultivation in Northern California, this essay explores the social category of the rural outlaw. It argues that outlawry consists not only in those whose actions are illegalized but also in the conditions through which racial capitalism accumulates and dispossesses at its various frontiers. Cannabis, before and after its legalization, gets caught up in various dynamics through which outlawry can be assessed.